Mother Stephanie Mohun, OP - Caspar, OP, Ruth; Graham, OP, Rosalie (Catholic Education: A Journal of Inquiry and Practice, 2006)
It is often stated that Catholic schools in the US were built on the foundation of the poverty of the vowed women religious. Dozens of communities fit this description, none more so than the Dominican Sisters of St. Mary of the Springs. Sister Stephane Mohun’s service as mother general spanned a period of tremendous growth in Catholic education at every level. Seeing to the ongoing education and professional preparation of the sisters, Mother Stephanie founded colleges, staffed schools, established missions, and provided leadership for Catholic education that continues to have an enduring legacy today.